EPIDEMIOLOGICAL PROFILE OF DENGUE CASES IN BRAZIL BETWEEN THE YEARS 2018 AND 2022 - Mendes de Carvalho, Thulio; Manoel Fortuna de Carvalho Neto; Álvaro Moura e Silva; Gabriel Ribeiro Learth; Igor Leal Pires Santos; Maria Antônia Oliveira Machado Pereira; Willimar Gleiser Schmidt Binsfeld; Aíne Moreira de Souza; Rhafaella Rocha Rosa de Lima; Laenio Souza Da Silva (Health and Society, 2023)
The present study aimed to analyze the epidemiological profile of dengue cases notified in Brazil between 2018 and 2022. This is a descriptive, retrospective, epidemiological study based on secondary data from the National Disease Notification Information System (SINAN). A total of 4,701,914 notified cases were analyzed in this period, with a focus on distribution by sex, age group, race/color, and region. There was a predominance of females (54.8%), young adults between 20 and 49 years old (53.6%), browns (36.7%) and whites (37.1%). The Southeast region had the most cases (43%), but the Northeast and Midwest also had high numbers. An expressive increasing trend was identified starting in 2019, with alarming peaks in 2021 and 2022. The study reveals that dengue persists as a serious public health problem in Brazil, making it essential to strengthen integrated strategies for vector prevention and control, epidemiological surveillance, community mobilization, and health education to reverse this trend.